Urgency of Legal Reform for Restructuring Non-Legal Entity Companies - Sultoni, Wahyudi; Dewi Suryandari, Wieke; Susilowati, Tri (Green Publisher Indonesia, 2024)
This research discusses the urgency of legal reform related to the restructuring of non-legal entity companies, such as trading businesses (UD), partnerships, and commandite partnerships (CV). The study highlights the legal uncertainties faced by these entities, which hinder their ability to adapt to market dynamics, access financial resources, and engage in strategic restructuring actions like mergers, acquisitions, and separations. Using a normative legal research method, this study analyzes existing legislative frameworks, including overlaps between the Micro, Small, and Medium Enterprises Law (UU UMKM) and the Job Creation Law, which create significant challenges for non-legal entities. The findings reveal that the absence of clear legal guidelines for restructuring leads to hesitancy in strategic decision-making and restricts these entities from accessing vital investment opportunities. The research concludes that comprehensive legal reform is essential to provide clear, specific regulations, establish structured partnerships, and create a conducive business environment for non-legal entities. These reforms will empower businesses to innovate, compete, and sustain growth while enhancing their overall market competitiveness.